Impact of Audit Committee Determinants on Financial Performance: Case of Tunisian Listed Banks - LETAIFA, Wissal BEN; ALI, Rayen BEN (Journal of Ecohumanism, 2024)
Purpose - The objective of this research is to study the relationship between audit committee determinants and corporate performance. To do this, we focus on the Tunisian context. Design/methodology/approach – Our research sample is made up of 16 banks operating in Tunisia observed over a period of five years (2017-2021) the paper uses a linear regression to investigate the association between the performance of the company and the determinants of audit committee. Findings - The results obtained show that the variable relating to the size of the audit committee has a positive influence on financial performance measured by Tobin’s Q. On the other hand, the variable relating to the number of meetings held by the audit committee has a negative impact on the financial performance of listed Tunisian companies.